PERANAN KEPRIBADIAN DALAM MENGHADAPI STRES YANG DIALAMI GURU DI SMPN 15 BEKASI - Nani Hanifah (Faktor Jurnal Ilmiah Kependidikan, 2015)
Abstract: This the research about “The role of personality in face stress experienced by teachers  at SMPN 15 Jakarta”. The research method used is qualitative method with descriptive approach. As data resource is 40 teachers  for fill the questionnaire of research and for interviuwed about stress and teachers personality. The research instrument is interview, questionnaire and observation. The result of research is the teachers at SMPN 15 Jakarta have type A personality and externalizer  personality and experience the stres in face of demans of the tasks as teacher. and the role of personality is if the teacher's personality is strong, patient, calm, relaxed, no rush, but with earnestnes, confident of success, sharing difficulties with other people and live with the unpleasant task, then the teacher can face the demands of the task and the stress calmly, so as not to cause fatal consequences for the physical and psychological.The final conclusion is that the personality is quite a role in dealing with the demands of the task and the stress experienced teachers. Key words:  personality, stress of the teachers.